Simple Synthesis of Sulfonyl Chlorides from Thiol Precursors and Derivatives by NaClO2-Mediated Oxidative Chlorosulfonation - Yang, Zhanhui; Zheng, Yongpeng; Xu, Jiaxi (Synlett, 2013)
A simple method to synthesize diverse sulfonyl chlorides through NaClO2-mediated oxidative chlorosulfonation of S-alkyl isothiourea salts is presented. The approach features safe operation, environmental friendliness, convenient purification procedures, and delivers high yields of up to 96%. The procedure is also applicable to substrates such as thiols, disulfides, thioacetates, and xanthates. It is a versatile and convenient method for the synthesis of various sulfonyl chlorides from different thiol precursors and derivatives.
Keywords: sulfonyl chloride; sodium chlorite; oxidative chlorosulfonation; synthetic methods; isothiourea